Uncovering the Value of ICT in Time Management for Implementation of OBE Courses - Balasangameshwara, Jasma (Journal of Engineering Education Transformations, 2015)
OBE is a reform approach to teaching/learning in which the decisions about the syllabus are determined by the outcomes that the students demonstrate at the end of the course. OBE requires continuous improvement to all phases of training thereby making it a recurring education transformation model. Due to its recurring nature, some of the major drawbacks of institutionalizing OBE are (1) major investment in time for rewriting all learning materials (2) time-consuming to implement OBE assessment methods due to its varied scope and variety of application (3) requires an intensive planning process with taxing activities on the instructors. Use of ICTs play a vital role in efficient time management and bringing about qualitative change in the application of OBE for designing effective courses. This article focuses on representing the potential of existing ICTs to the application of OBE in the design of a post-graduate course prescribed by VTU, India for CS&E program. Some ofthe existing ICTs that can be used for effectively implementing the three key OBE elements i.e. content, assessment/feedback and outcomes’ achievement evaluation is presented along with an extensive comparison in terms of time investment when practiced with and without the use of ICTs. The conclusion drawn after analysis of the time management using ICTs is that they significantly decrease the time spent for application of OBE in analysis of courses. Hence, it is recommended to use one main ICT that is exclusively designed for effective OBE implementation along with other ICTs to significantly save time for other academic & research activities.